DYSPHAGIA AFTER LAPAROSCOPIC TOTAL FUNDOPLICATION: anterior or posterior gastric wall fundoplication? - BONADIMAN,Adorísio (2014)
ContextThe occurrence of severe dysphagia after laparoscopic total fundoplication is currently an important factor associated with loss of quality of life in patients undergoing this modality of treatment for gastroesophageal reflux disease.ObjectivesCompare the incidence and evaluate the causes of severe postoperative dysphagia in patients undergoing laparoscopic total fundoplication (LTF) without short gastric vessels division, using the anterior gastric wall (Rossetti LTF) or anterior and posterior gastric walls (Nissen LTF).MethodsAnalysis of the data of 289 patients submitted to LTF without short gastric vessels division from January 2004 to January 2012, with a minimum follow-up of 6 months. Patients were divided in Group 1 (Rossetti LTF – n = 160) and Group 2 (Nissen LTF – n = 129).ResultsThe overall incidence of severe postoperative dysphagia was 3.11% (4.37% in group 1 and 1.55% in group 2; P = 0.169). The need for surgical treatment of dysphagia was 2.5% in group 1 and 0.78% in group 2 (= 0.264). Distortions of the fundoplication were identified as possible causes of the dysphagia in all patients taken to redo fundoplication after Rossetti LTF. No wrap distortion was seen in redo fundoplication after Nissen LTF.ConclusionsThe overall incidence of severe postoperative dysphagia did not differ on the reported techniques. Only Rossetti LTF was associated with structural distortion of the fundoplication that could justify the dysphagia.